Scenario Planning Analysis Case Study: PT Swara Milliard Artha - Wiharto, Dila Fiona; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2014)
Abstractâ€”This research explained about the application form of scenario planning analysis as solution for PT. Swara Milliard Artha 99ers Radio Bandung, which was formatted as a teenage radio station and ranked on number one teenage radio station in Bandung since its first aired until now. However, to help keep the existence on the business industry, 99ers Radio has several internal and external problems that effect on company's survival later on. The technique found in this approach is to collect data and information to be analyzed in order to generate predictions as a preparation for decision-making process. This approach give an overview of early warning, implications and options in each scenario drawn from the analysis of external and internal as recommendation for the organization which could be properly used as a guide in determining and developing company's business strategy.Â Keywords: Broadcast Radio Industry, 99ers Radio, Scenario Planning, Strategic Decision